A cobalt-ruthenium oxide electrode, a preparation method and application thereof

CN122879741APending Publication Date: 2026-10-09DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611390414.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-09

Smart Images

  • Figure CN122879741A_ABST
    Figure CN122879741A_ABST
Patent Text Reader

Abstract

The application discloses a cobalt-ruthenium oxide electrode and a preparation method and application thereof, and belongs to the technical field of hydrogen production by water electrolysis. The cobalt-ruthenium oxide electrode is prepared by using a conductive material as a support substrate and a cobalt-ruthenium oxide as a catalytic layer. A precursor solution is prepared by mixing a cobalt precursor, a ruthenium precursor and citric acid, and is coated on the surface of the support substrate. The coated support substrate is dried at a constant temperature and is calcined in an air atmosphere, so that a cobalt-ruthenium oxide catalytic layer rich in oxygen vacancies and having strong hetero-metal coupling is in-situ synthesized on the surface of the support substrate. The prepared cobalt-ruthenium oxide electrode can be directly used as an alkaline water electrolysis hydrogen evolution electrode. The catalyst preparation method is simple and controllable. The prepared cobalt-ruthenium oxide electrode has unique Co-Ru synergistic and oxygen vacancy structures, exhibits an ultra-low hydrogen evolution overpotential, excellent high current density activity and a stability of up to thousands of hours in an alkaline medium, and provides a new material support for industrialization of anion exchange membrane water electrolysis hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrolytic hydrogen production catalysis technology, specifically relating to a cobalt ruthenium oxide electrode, its preparation method, and its application. Background Technology

[0002] As the global energy structure shifts towards cleaner energy, hydrogen energy is considered an ideal sustainable energy carrier due to its high energy density and zero carbon emissions. Hydrogen production via water electrolysis powered by renewable electricity is a key technological pathway for achieving large-scale green hydrogen production. Among various water electrolysis technologies, anion exchange membrane electrolysis (HEMWE) combines the low cost of alkaline water electrolysis with the high efficiency and compactness of proton exchange membrane electrolysis, enabling industrial-grade current densities (>1 A / cm²). -2 Operating under alkaline conditions, the hydrogen evolution reaction (HER) has great development potential. However, the kinetics of HER are slow due to the additional water dissociation step involved. In addition, the high cost and scarcity of currently widely used precious metal catalysts (especially platinum-based materials) severely restrict the large-scale commercial deployment of HER.

[0003] Ruthenium (Ru) is considered one of the most promising alternatives to platinum-based catalysts due to its similar hydrogen adsorption free energy to platinum and its relatively low price. However, metallic ruthenium is prone to surface reconstruction, poisoning, and dissolution in alkaline electrolytes, exhibiting poor stability. In contrast, ruthenium dioxide (RuO2) has better thermodynamic stability, but its low defect density and limited water adsorption sites result in weak water activation ability. To address this issue, coupling RuO2 with transition metal oxides has become an important strategy for improving performance. Cobalt tetroxide (Co3O4) is particularly promising due to its tunable Co... 3+ / Co 2+ Redox pairs can promote the formation of oxygen vacancies and drive the redistribution of interfacial charges, which is beneficial to the adsorption and dissociation of water, making them ideal candidate materials for composite with Ru-based catalysts.

[0004] However, the reported methods for preparing cobalt-ruthenium oxide electrodes currently have two main problems: First, the products obtained by hydrothermal methods or precipitation-annealing methods (such as patents CN118880391A and CN117265585A) are powders, which require coating with binders. The process is cumbersome and can easily lead to the embedding of active sites and weak interfacial bonding. Second, although the in-situ hydrothermal method can prepare self-supporting electrodes (CN119980295A), it requires a strong acid medium (18wt% hydrochloric acid, etched at 90℃) and a long reaction time (20 h), which are harsh conditions.

[0005] Therefore, developing a simple method for preparing cobalt ruthenium oxide self-supporting electrodes that can be grown in situ under mild conditions without binders is of great value for overcoming the shortcomings of existing technologies and promoting the practical application of anion exchange membrane water electrolysis for hydrogen production. Summary of the Invention

[0006] The present invention aims to provide a cobalt-ruthenium oxide electrode, its preparation method, and its applications. Using a conductive substrate as a carrier, and non-noble metal cobalt salt and noble metal ruthenium salt as raw materials, and citric acid as a complexing agent, a cobalt-ruthenium bimetallic oxide catalytic layer with strong Co-Ru electronic coupling and abundant oxygen vacancies is synthesized in situ on the substrate surface through a coating-drying-calcination process. The resulting electrode can be directly used as an alkaline HER cathode, exhibiting ultra-low overpotential, excellent high current density performance, and outstanding long-term operational stability.

[0007] To achieve the above objectives, the technical solution of the present invention is as follows: This invention provides a method for preparing a cobalt-ruthenium oxide electrode, comprising the following steps: (1) Dissolve and mix the cobalt precursor, ruthenium precursor and citric acid, then heat and stir to obtain a precursor solution; (2) The precursor solution obtained in step (1) is coated on the surface of the support substrate and then dried at a constant temperature to obtain the electrode precursor; (3) The electrode precursor obtained in step (2) is calcined in an oxygen-containing atmosphere to obtain a cobalt ruthenium oxide electrode.

[0008] In the above technical solution, further, in step (1), the cobalt precursor is one of cobalt nitrate, cobalt acetate, cobalt chloride, and cobalt sulfate; The ruthenium precursor is one of ruthenium trichloride, ruthenium nitrite nitrate, ruthenium nitrate, and ruthenium acetate; The molar ratio of the cobalt precursor to the ruthenium precursor is 8:1 to 0.5:1; The molar ratio of citric acid to the total molar ratio of cobalt ions and ruthenium ions is 1:1 to 2:1.

[0009] In the above technical solution, further, in step (1), the heating and stirring temperature is 50~80℃ and the stirring time is 0.5~2h.

[0010] In the above technical solution, further, in step (2), the supporting substrate is pretreated before use. The pretreatment steps include: ultrasonically washing the conductive substrate with organic solvent and ultrapure water in sequence, and then drying it. The organic solvent is one or more of methanol, ethanol, acetone, isopropanol, ethylene glycol, DMF, diethyl ether, toluene, chloroform, n-hexane, cyclohexane, ethyl acetate, dichloromethane, acetonitrile, and tetrahydrofuran; The drying temperature is 60~120℃, and the drying time is 10~24h.

[0011] In the above technical solution, further, in step (2), the supporting substrate is one of carbon paper, carbon cloth, conductive glass, nickel felt, titanium mesh, and nickel foam.

[0012] In the above technical solution, further, in step (2), the coating method is one of drip coating, scraping coating, spin coating, and spray coating.

[0013] In the above technical solution, further, in step (2), the drying temperature is 100~150℃.

[0014] In the above technical solution, further, in step (3), the calcination temperature is 250~400℃, the calcination time is 2~6h, and the heating rate is 2~10℃ / min; The oxygen-containing atmosphere is air, or an O2 / N2 mixture with an oxygen volume fraction of 10% to 50%, or an O2 / Ar mixture with an oxygen volume fraction of 10% to 50%.

[0015] Another aspect of the present invention provides a cobalt-ruthenium oxide electrode prepared by the above-described preparation method. The electrode comprises a supporting substrate and a catalyst layer loaded on the surface of the supporting substrate. The catalyst layer is cobalt-ruthenium oxide, wherein Ru is incorporated into the Co3O4 lattice. The loading amount of the catalyst layer on the supporting substrate is 0.25~1 mg cm⁻¹. -2 .

[0016] The present invention also provides an application of the above-mentioned cobalt ruthenium oxide electrode, wherein the electrode is used in the alkaline water electrolysis hydrogen evolution reaction as the cathode of anion exchange membrane water electrolysis.

[0017] The catalytic performance of the above cobalt-ruthenium oxide electrode in water electrolysis for hydrogen production was tested. The cobalt-ruthenium oxide electrode prepared by the above method was used as the working electrode, and its catalytic performance for hydrogen evolution in an alkaline solution system was tested by electrochemical methods: Step 1) A three-electrode testing system was set up to evaluate the electrocatalytic hydrogen evolution performance of the prepared cobalt-ruthenium oxide electrode: the prepared cobalt-ruthenium oxide electrode was directly used as the working electrode, a graphite rod or platinum sheet was used as the counter electrode, and a mercury / mercury oxide electrode was used as the reference electrode. 1M KOH solution was used as the electrolyte to test the electrocatalytic hydrogen evolution performance of the prepared cobalt-ruthenium oxide electrode in an alkaline electrolyte system; Step 2) The three-electrode system was connected to an electrochemical workstation to conduct performance tests on the cobalt-ruthenium oxide electrode using electrochemical methods: the intrinsic activity of the cobalt-ruthenium oxide electrode was evaluated using linear sweep voltammetry and cyclic voltammetry; the impedance properties and charge transfer behavior of the cobalt-ruthenium oxide electrode were evaluated using AC impedance measurement; the stability of the cobalt-ruthenium oxide electrode was evaluated using chronopotential method, chronocurrent method and accelerated durability cycle test; hydrogen was collected by water displacement and the Faraday efficiency was calculated; the test results can directly illustrate the catalytic index and overall performance of the prepared cobalt-ruthenium oxide electrode.

[0018] The above-mentioned electrode was used as the cathode and assembled with the anode and anion exchange membrane to form a membrane electrode assembly, thus constructing an anion exchange membrane water electrolysis single cell. Polarization curves and constant current stability tests were conducted in 60℃ and 1 M KOH electrolyte to evaluate its industrial application potential in actual electrolyzers.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention utilizes the complexing effect of citric acid to form stable soluble complexes with cobalt and ruthenium metal ions, achieving molecular-level uniform mixing. This allows Ru atoms to be uniformly embedded in the Co3O4 lattice during calcination. On one hand, this increases the number of Co-O-Ru interfaces, enabling Ru active sites to fully accept electronic regulation from Co and fully leverage the synergistic catalytic effect of cobalt and ruthenium. On the other hand, it effectively inhibits the dissolution and aggregation of ruthenium during long-term electrolysis, thus ensuring the structural stability of the electrode during long-term operation. In addition, the carbon skeleton of citric acid slowly oxidizes and decomposes during calcination, serving both pore-forming and oxygen-vacancy-inducing functions. The pores formed by its decomposition facilitate the exposure of active sites and mass transfer. Furthermore, the decomposition process consumes local oxygen and generates reducing intermediates, creating a locally oxygen-deficient environment in the oxide formation process, which is conducive to the generation of oxygen vacancies. Simultaneously, the lattice distortion caused by Ru substituting Co sites further promotes the preferential enrichment of these oxygen vacancies near the Co-O-Ru interface, providing efficient adsorption and activation sites for water molecules and promoting the water dissociation step.

[0020] 2. In the oxide electrode prepared by the method of the present invention, cobalt-based oxide serves as the main framework and has tunable Co content. 3+ / Co 2+Redox pairs that can accommodate Ru 4+ Substitution can transfer electrons to Ru sites, inhibiting their over-oxidation; ruthenium provides platinum-like hydrogen adsorption free energy, compensating for the weak hydrogen adsorption of cobalt-based oxides. The resulting electrode exhibits ultra-low hydrogen evolution overpotential and excellent long-term stability in alkaline media, and can operate stably for thousands of hours at industrial-grade current densities, outperforming most cobalt-based and ruthenium-based alkaline hydrogen evolution electrode materials reported to date.

[0021] 3. This invention allows for flexible control over the type of conductive substrate, the molar ratio of cobalt to ruthenium, the ratio of citric acid to total metal ions, precursor heating and stirring conditions, and calcination conditions, thereby optimizing the electronic structure and catalytic performance of the electrode over a wide range. The molar ratio of cobalt to ruthenium directly determines the Co content. 3+ / Co 2+ The ratio and oxygen vacancy concentration are optimally balanced within the scope of this invention, taking into account both water activation and hydrogen adsorption functions. When the molar ratio of citric acid to total metal ions is 1:1 to 2:1, cobalt and ruthenium ions are fully complexed, the solution is homogeneous and stable, and the carbon skeleton of citric acid is slowly oxidized and decomposed during calcination, generating an appropriate amount of oxygen vacancies with little carbon residue. If the ratio is too low, the complexation is insufficient, and metal ions are prone to precipitation and aggregation. If the ratio is too high, the carbon residue increases, reducing conductivity and covering active sites. A calcination temperature of 250 to 400°C can fully remove organic templates and form a stable Co3O4 phase, while retaining a high concentration of oxygen vacancies. If the temperature is too low, the organic matter decomposition is incomplete, and if the temperature is too high, the oxygen vacancies are annihilated and the particles are sintered.

[0022] 4. This invention utilizes a citric acid-assisted in-situ pyrolysis process to grow oxygen-rich vacancy-rich CoRuO in situ on a conductive support substrate. x A catalytic layer is used to prepare a self-supporting electrode. Using non-precious metal cobalt and precious metal ruthenium as raw materials, this method offers a significant cost advantage over platinum-based catalysts and can be widely used in anion exchange membrane water electrolysis devices, making it one of the ideal non-platinum electrode materials to replace platinum-based catalysts. Furthermore, this method consists of simple solution coating and calcination steps, requiring no pre-synthesized powders or any binders. This not only makes the process simple and controllable, safe to operate, and environmentally friendly, but also avoids the problems of binder embedding of active sites and increased interfacial resistance in traditional coating methods. Simultaneously, the catalytic layer prepared by this invention is firmly bonded to the substrate and is not easily detached under high current densities. Attached Figure Description

[0023] Figure 1 The XRD patterns of the oxide electrodes prepared in Example 1 and Comparative Example 2 are shown. Figure 2 TEM images and particle size distribution statistics of the cobalt ruthenium oxide electrode prepared in Example 1; Figure 3 HRTEM image of the cobalt-ruthenium oxide electrode prepared in Example 1; Figure 4 Comparison of EPR spectra of Example 1, Comparative Example 2, and Comparative Example 3; Figure 5 This is a comparison of the HER polarization curves of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 in 1M KOH solution; Figure 6 This is a comparison of the HER polarization curves of Examples 1, 2, 3, and 6 in 1M KOH solution; Figure 7 This is a comparison chart of the Tafel slopes for Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. Figure 8 This is a comparison chart of Tafel slopes for Examples 1, 2, 3, and 6. Figure 9 The polarization curves are for HEMWE single cells of Example 1 and Comparative Example 1. Figure 10 The HEMWE single cell of Example 1 at 1Acm -2 Constant current stability test curve under current density. Detailed Implementation

[0024] The technical solutions and effects of the present invention are further illustrated below through specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.

[0025] Unless otherwise specified, all materials used in the embodiments of this invention are commercially available.

[0026] Example 1 (1) Pretreatment of carbon paper substrate: Cut the carbon paper into uniform size, and ultrasonically clean it in acetone, ethanol and ultrapure water for 15 min each to remove surface contaminants. After cleaning, place the carbon paper in an 80℃ oven to dry for 12 h for later use. (2) Preparation of precursor solution: Accurately weigh 2 mmol cobalt nitrate and 2 mmol ruthenium trichloride, dissolve them in 40 mL of ultrapure water, stir magnetically until completely dissolved, add 4 mmol citric acid, continue stirring for 30 min, transfer the mixed solution to a 60 °C water bath, and stir magnetically for 1 h at 60 °C to allow the metal ions to fully complex with the citric acid, and obtain a homogeneous, transparent reddish-brown precursor solution; (3) Preparation of electrode precursor: The precursor solution obtained in step (2) was pipetted and uniformly coated onto the surface of the pretreated carbon paper. The coated carbon paper was placed in a drying oven and dried at 150°C for 2 hours. The solvent evaporated slowly, and the metal... Citric acid complex is uniformly cured on the surface of carbon fiber to obtain electrode precursor; (4) Calcination: The dried electrode precursor was placed in a tube furnace and heated to 300°C at a rate of 5°C / min under an air atmosphere. The mixture was then calcined at this temperature for 4 hours. After the reaction was completed, the furnace was cooled to room temperature to obtain oxygen-vacancy-rich cobalt ruthenium oxide (CoRuO2). x ) electrode, wherein CoRuO x The loading amount on the carbon paper substrate was 0.3 mg / cm³. -2 The loading of the precious metal Ru on the carbon paper substrate was 0.15 mg / cm³. -2 .

[0027] Figure 1 The X-ray diffraction (XRD) pattern of the electrode obtained in this embodiment shows typical diffraction peaks characteristic of the Co3O4 cubic spinel phase. No diffraction peaks of RuO2 or metallic Ru were observed, indicating that Ru has been highly dispersed into the Co3O4 lattice. Figure 2 Transmission electron microscopy (TEM) images and particle size distribution statistics show that nanoparticles with an average particle size of 3.58 nm are uniformly distributed on the electrode surface. Figure 3 The spacing of the crystal plane stripes in the high-resolution transmission electron microscope (HRTEM) image corresponds to the (311) and (400) crystal planes of Co3O4. Figure 4 Electron paramagnetic resonance (EPR) spectroscopy showed that the oxygen vacancy content of the electrode in this embodiment was much higher than that of pure Co3O4 (Comparative Example 2) and pure RuO2 (Comparative Example 3).

[0028] Example 2 (1) Pretreatment of carbon paper substrate: Cut the carbon paper into uniform size, and ultrasonically clean it in acetone, ethanol and ultrapure water for 15 min each to remove surface contaminants. After cleaning, place the carbon paper in an 80℃ oven to dry for 12 h for later use. (2) Preparation of precursor solution: Accurately weigh 6 mmol cobalt nitrate and 2 mmol ruthenium trichloride, dissolve them in 80 mL of ultrapure water, stir magnetically until completely dissolved, add 8 mmol citric acid, continue stirring for 30 min, transfer the mixed solution to a 60 °C water bath, and stir magnetically for 1 h at 60 °C to allow the metal ions to fully complex with the citric acid, and obtain a homogeneous, transparent reddish-brown precursor solution; (3) Preparation of electrode precursor: The precursor solution obtained in step (2) was pipetted and uniformly coated onto the surface of the treated carbon paper. The coated carbon paper was placed in a drying oven and dried at 150°C for 2 hours. The solvent evaporated slowly, and the metal... Citric acid complex is uniformly cured on the surface of carbon fiber to obtain electrode precursor; (4) Calcination: The dried electrode precursor was placed in a tube furnace and heated to 300°C at a rate of 5°C / min under an air atmosphere. The mixture was then calcined at this temperature for 4 hours. After the reaction was completed, the mixture was cooled to room temperature with the furnace to obtain oxygen-rich vacancy CoRuO. x Electrode, wherein CoRuO x The loading amount on the carbon paper substrate was 0.5 mg cm. -2 The loading of the precious metal Ru on the carbon paper substrate was 0.15 mg / cm³. -2 .

[0029] Example 3 (1) Pretreatment of carbon paper substrate: Cut the carbon paper into uniform size, and ultrasonically clean it in acetone, ethanol and ultrapure water for 15 min each to remove surface contaminants. After cleaning, place the carbon paper in an 80℃ oven to dry for 12 h for later use. (2) Preparation of precursor solution: Accurately weigh 16 mmol cobalt nitrate and 2 mmol ruthenium trichloride, dissolve them in 180 mL of ultrapure water, stir magnetically until completely dissolved, add 18 mmol citric acid, continue stirring for 30 min, transfer the mixed solution to a 60 °C water bath, and stir magnetically for 1 h at 60 °C to allow the metal ions to fully complex with the citric acid, and obtain a homogeneous, transparent reddish-brown precursor solution; (3) Preparation of electrode precursor: The precursor solution obtained in step (2) was pipetted and uniformly coated onto the surface of the treated carbon paper. The coated carbon paper was placed in a drying oven and dried at 150°C for 2 hours. The solvent evaporated slowly, and the metal... Citric acid complex is uniformly cured on the surface of carbon fiber to obtain electrode precursor; (4) Calcination: The dried electrode precursor was placed in a tube furnace and heated to 300°C at a rate of 5°C / min under an air atmosphere. The mixture was then calcined at this temperature for 4 hours. After the reaction was completed, the mixture was cooled to room temperature with the furnace to obtain oxygen-rich vacancy CoRuO. x Electrode, wherein CoRuO x The loading amount on the carbon paper substrate was 1 mg cm. -2 The loading of the precious metal Ru on the carbon paper substrate was 0.15 mg / cm³. -2 .

[0030] Example 4 (1) Pretreatment of carbon paper substrate: Cut the carbon paper into uniform size, and ultrasonically clean it in acetone, ethanol and ultrapure water for 15 min each to remove surface contaminants. After cleaning, place the carbon paper in an 80℃ oven to dry for 12 h for later use. (2) Preparation of precursor solution: Accurately weigh 2 mmol cobalt chloride and 2 mmol ruthenium nitrate, dissolve them in 40 mL of ultrapure water, stir magnetically until completely dissolved, add 4 mmol citric acid, continue stirring for 30 min, transfer the mixed solution to a 60 °C water bath, and stir magnetically for 1 h at 60 °C to allow the metal ions to fully complex with the citric acid, and obtain a homogeneous, transparent reddish-brown precursor solution; (3) Preparation of electrode precursor: The above precursor solution was pipetted and uniformly applied to the surface of the treated carbon paper. The coated carbon paper was placed in a drying oven and dried at 150°C for 2 hours. The solvent evaporated slowly, and the metal... Citric acid complex is uniformly cured on the surface of carbon fiber to obtain electrode precursor; (4) Calcination: The dried electrode precursor was placed in a tube furnace and heated to 400°C at a rate of 5°C / min under an air atmosphere. The mixture was then calcined at this temperature for 4 hours. After the reaction was completed, the mixture was cooled to room temperature with the furnace to obtain oxygen-rich vacancy CoRuO. x Electrode, wherein CoRuO x The loading amount on the carbon paper substrate was 0.3 mg / cm³. -2 The loading of the precious metal Ru on the carbon paper substrate was 0.15 mg / cm³. -2 .

[0031] Example 5 (1) Pretreatment of nickel felt substrate: cut the nickel felt into uniform size, and ultrasonically clean it in acetone, ethanol and ultrapure water for 15 min each to remove surface contaminants. After cleaning, place the carbon paper in an 80℃ oven to dry for 12 h for later use. (2) Preparation of precursor solution: Accurately weigh 2 mmol cobalt nitrate and 2 mmol ruthenium trichloride, dissolve them in 40 mL of ultrapure water, stir magnetically until completely dissolved, add 4 mmol citric acid, continue stirring for 30 min, transfer the mixed solution to a 60 °C water bath, stir magnetically and heat for 1 h to allow the metal ions to fully complex with the citric acid, and obtain a homogeneous, transparent reddish-brown precursor solution; (3) Preparation of electrode precursor: The precursor solution obtained in step (2) was pipetted and uniformly coated onto the surface of the treated nickel felt. The coated nickel felt was placed in a drying oven and dried at 150°C for 2 hours. The solvent evaporated slowly, and the metal... Citric acid complex is uniformly cured on the surface of carbon fiber to obtain electrode precursor; (4) Calcination: The dried electrode precursor was placed in a tube furnace and heated to 300°C at a rate of 5°C / min under an air atmosphere. The mixture was then calcined at this temperature for 4 hours. After the reaction was completed, the mixture was cooled to room temperature with the furnace to obtain oxygen-rich vacancy CoRuO. x Electrode, wherein CoRuO xThe loading amount on the carbon paper substrate was 0.3 mg / cm³. -2 The loading of the precious metal Ru on the carbon paper substrate was 0.15 mg / cm³. -2 .

[0032] Example 6 (1) Pretreatment of carbon paper substrate: Cut the carbon paper into uniform size, and ultrasonically clean it in acetone, ethanol and ultrapure water for 15 min each to remove surface contaminants. After cleaning, place the carbon paper in an 80℃ oven to dry for 12 h for later use. (2) Preparation of precursor solution: Accurately weigh 1 mmol cobalt nitrate and 2 mmol ruthenium trichloride, dissolve them in 30 mL of ultrapure water, stir magnetically until completely dissolved, add 6 mmol citric acid, continue stirring for 30 min, transfer the mixed solution to a 60 °C water bath, and stir magnetically for 1 h at 60 °C to allow the metal ions to fully complex with the citric acid, and obtain a homogeneous, transparent reddish-brown precursor solution; (3) Preparation of electrode precursor: The precursor solution obtained in step (2) was pipetted and uniformly coated onto the surface of the treated carbon paper. The coated carbon paper was placed in a drying oven and dried at 150°C for 2 hours. The solvent evaporated slowly, and the metal... Citric acid complex is uniformly cured on the surface of carbon fiber to obtain electrode precursor; (4) Calcination: The dried electrode precursor was placed in a tube furnace and heated to 250°C at a rate of 5°C / min under an air atmosphere. The mixture was then calcined at this temperature for 4 hours. After the reaction was completed, the mixture was cooled to room temperature with the furnace to obtain oxygen-rich vacancy CoRuO. x Electrode, wherein CoRuO x The loading amount on the carbon paper substrate was 0.25 mg / cm³. -2 The loading of the precious metal Ru on the carbon paper substrate was 0.15 mg / cm³. -2 .

[0033] Comparative Example 1 Commercial Pt / C electrode. A commercial 20 wt% Pt / C catalyst was dispersed in water, isopropanol, and a 5% Nafion solution, ultrasonically slurried, and then drop-coated onto pretreated carbon paper. The Pt loading was approximately 0.15 mg / cm³. -2 air dry.

[0034] Comparative Example 2 The comparative catalyst was prepared according to Example 1, referred to as Comparative Example 2, except that ruthenium salt was not added to the precursor solution.

[0035] (1) Pretreatment of carbon paper substrate: Cut the carbon paper into uniform size, and ultrasonically clean it in acetone, ethanol and ultrapure water for 15 min each to remove surface contaminants. After cleaning, place the carbon paper in an 80℃ oven to dry for 12 h for later use. (2) Preparation of precursor solution: Accurately weigh 4 mmol of cobalt nitrate and dissolve it in 40 mL of ultrapure water. Stir magnetically until completely dissolved, add 4 mmol of citric acid, and continue stirring for 30 min. Transfer the mixed solution to a 60 °C water bath and heat magnetically for 1 h to allow the metal ions to fully complex with the citric acid, resulting in a homogeneous and transparent reddish-brown precursor solution. (3) Preparation of electrode precursor: The precursor solution obtained in step (2) was pipetted and uniformly coated onto the surface of the treated carbon paper. The coated carbon paper was placed in a drying oven and dried at 150°C for 2 hours. The solvent evaporated slowly, and the metal... Citric acid complex is uniformly cured on the surface of carbon fiber to obtain electrode precursor; (4) Calcination: The dried electrode precursor was placed in a tube furnace and heated to 300°C at a rate of 5°C / min under an air atmosphere. The mixture was then calcined at this temperature for 4 hours. After the reaction was complete, the furnace was cooled to room temperature to obtain the Co3O4 electrode, in which the loading of Co3O4 on the carbon paper substrate was 0.2 mg / cm³. -2 The loading amount of Co on the carbon paper substrate was 0.15 mg / cm³. -2 .

[0036] Comparative Example 3 The comparative catalyst was prepared according to Example 1, referred to as Comparative Example 3, except that no cobalt salt was added to the precursor solution.

[0037] (1) Pretreatment of carbon paper substrate: Cut the carbon paper into uniform size, and ultrasonically clean it in acetone, ethanol and ultrapure water for 15 min each to remove surface contaminants. After cleaning, place the carbon paper in an 80℃ oven to dry for 12 h for later use. (2) Preparation of precursor solution: Accurately weigh 2 mmol of ruthenium chloride and dissolve it in 20 mL of ultrapure water. Stir magnetically until completely dissolved, add 2 mmol of citric acid, and continue stirring for 30 min. Transfer the mixed solution to a 60 °C water bath and heat magnetically for 1 h to allow the metal ions to fully complex with the citric acid, resulting in a homogeneous, transparent reddish-brown precursor solution. (3) Preparation of electrode precursor: The precursor solution obtained in step (2) was pipetted and uniformly coated onto the surface of the treated carbon paper. The coated carbon paper was placed in a drying oven and dried at 150°C for 2 hours. The solvent evaporated slowly, and the metal... Citric acid complex is uniformly cured on the surface of carbon fiber to obtain electrode precursor; (4) Calcination: The dried electrode precursor was placed in a tube furnace and heated to 300°C at a rate of 5°C / min under air atmosphere. The mixture was then calcined at this temperature for 4 hours. After the reaction was complete, the furnace was cooled to room temperature to obtain the RuO2 electrode, wherein the RuO2 loading on the carbon paper substrate was 0.2 mg / cm³.-2 The loading of the precious metal Ru on the carbon paper substrate was 0.15 mg / cm³. -2 .

[0038] Comparative Example 4 (1) Pretreatment of carbon paper substrate: Cut the carbon paper into uniform size, and ultrasonically clean it in acetone, ethanol and ultrapure water for 15 min each to remove surface contaminants. After cleaning, place the carbon paper in an 80℃ oven to dry for 12 h for later use. (2) Preparation of precursor solution: Accurately weigh 20 mmol cobalt nitrate and 2 mmol ruthenium trichloride, dissolve them in 220 mL of ultrapure water, stir magnetically until completely dissolved, add 22 mmol citric acid, continue stirring for 30 min, transfer the mixed solution to a 60 °C water bath, and stir magnetically for 1 h at 60 °C to allow the metal ions to fully complex with the citric acid, and obtain a homogeneous, transparent reddish-brown precursor solution; (3) Preparation of electrode precursor: The precursor solution obtained in step (2) was pipetted and uniformly coated onto the surface of the pretreated carbon paper. The coated carbon paper was placed in a drying oven and dried at 150°C for 2 hours. The solvent evaporated slowly, and the metal... Citric acid complex is uniformly cured on the surface of carbon fiber to obtain electrode precursor; (4) Calcination: The dried electrode precursor was placed in a tube furnace and heated to 300°C at a rate of 5°C / min under an air atmosphere. The mixture was then calcined at this temperature for 4 hours. After the reaction was completed, the furnace was cooled to room temperature to obtain oxygen-rich vacancy cobalt ruthenium oxide (CoRuO2). x The electrode contains a noble metal Ru loaded at a concentration of 0.15 mg / cm³ on a carbon paper substrate. -2 .

[0039] Comparative Example 5 (1) Pretreatment of carbon paper substrate: Cut the carbon paper into uniform size, and ultrasonically clean it in acetone, ethanol and ultrapure water for 15 min each to remove surface contaminants. After cleaning, place the carbon paper in an 80℃ oven to dry for 12 h for later use. (2) Preparation of precursor solution: Accurately weigh 2 mmol cobalt nitrate and 2 mmol ruthenium trichloride, dissolve them in 40 mL of ultrapure water, stir magnetically until completely dissolved, add 4 mmol citric acid, continue stirring for 30 min, transfer the mixed solution to a 60 °C water bath, and stir magnetically for 1 h at 60 °C to allow the metal ions to fully complex with the citric acid, and obtain a homogeneous, transparent reddish-brown precursor solution; (3) Preparation of electrode precursor: The precursor solution obtained in step (2) was pipetted and uniformly coated onto the surface of the pretreated carbon paper. The coated carbon paper was placed in a drying oven and dried at 150°C for 2 hours. The solvent evaporated slowly, and the metal... Citric acid complex is uniformly cured on the surface of carbon fiber to obtain electrode precursor; (4) Calcination: The dried electrode precursor was placed in a tube furnace and heated to 500°C at a rate of 5°C / min under an air atmosphere. The mixture was then calcined at this temperature for 4 hours. After the reaction was completed, the furnace was cooled to room temperature to obtain oxygen-rich vacancy cobalt ruthenium oxide (CoRuO2). x The electrode contains a noble metal Ru loaded at a concentration of 0.15 mg / cm³ on a carbon paper substrate. -2 .

[0040] Test Example 1 Electrochemical methods were used to test the catalytic performance of the electrodes prepared in Examples 1-3, Example 6, and Comparative Examples 1-5 in an alkaline solution system for the electrocatalytic evolution of hydrogen. The electrodes obtained in Examples 1-3, Example 6, and Comparative Examples 1-5 were used as working electrodes, platinum sheets as counter electrodes, mercury / mercuric oxide electrodes as reference electrodes, and 1M KOH solution as the electrolyte. The test results are shown in Table 1.

[0041] Table 1. Catalytic performance of electrodes prepared in the examples and comparative examples for electrocatalytic hydrogen evolution in alkaline solution systems.

[0042] like Figure 5-6 As shown, the oxygen-rich vacancy CoRuO prepared in Examples 1-3 x The electrode's hydrogen evolution performance in alkaline media is close to that of commercial Pt / C (Comparative Example 1), with a 10 mA cm⁻¹. -2 The overpotential is 26mV, which is far superior to the single metal oxide electrodes of Comparative Examples 2 and 3, as well as Comparative Examples 4 and 5, which are outside the scope of protection of this invention; such as Figure 7-8 As shown, the Tafel slope of the electrode obtained in Example 1 is 54 mVdec. -1 Therefore, it can be seen that the electrode of Example 1 has particularly outstanding hydrogen evolution performance at higher current densities.

[0043] Test Example 2 The electrodes obtained in Example 1 and Comparative Example 1 were used as cathodes and assembled with a NiFe-LDH anode (prepared according to the literature "Construction of orderly hierarchical FeOOH / NiFe layered double hydroxides supported on cobaltous carbonate hydroxide nanowire arrays for a highly efficient oxygen evolution reaction") and an e-PTFE anion exchange membrane (Shanghai Hancheng Technology) to form a membrane electrode assembly, thus constructing an anion exchange membrane electrolysis water single cell (HEMWE). Polarization curves and constant current stability were tested at 60℃ in 1 M KOH electrolyte.

[0044] like Figure 9 As shown, the performance of Example 1 is significantly better than that of the comparative battery with Pt / C as the cathode, and it can operate stably for a long time at industrial-grade current densities with low voltage decay (e.g., Figure 10 (As shown).

[0045] As can be seen from the system comparison between the above embodiments and comparative examples, the citric acid-assisted in-situ preparation method proposed in this invention can accurately construct the interface structure of Co-Ru dual sites and oxygen vacancies. The resulting electrode exhibits significantly better comprehensive performance than single oxides and commercial Pt / C in alkaline HER, especially in terms of high current density and long-term stability, providing key material and process support for the practical application of anion exchange membrane water electrolysis technology.

[0046] The above description is merely a preferred embodiment of the present invention and is not intended to limit the implementation of the present invention. Any adjustments or substitutions made without departing from the concept and scope of the claims should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a cobalt-ruthenium oxide electrode, characterized in that, Includes the following steps: (1) Dissolve and mix the cobalt precursor, ruthenium precursor and citric acid, then heat and stir to obtain a precursor solution; (2) The precursor solution obtained in step (1) is coated on the surface of the support substrate and then dried at a constant temperature to obtain the electrode precursor; (3) The electrode precursor obtained in step (2) is calcined in an oxygen-containing atmosphere to obtain a cobalt ruthenium oxide electrode.

2. The preparation method according to claim 1, characterized in that, In step (1), the cobalt precursor is one of cobalt nitrate, cobalt acetate, cobalt chloride, and cobalt sulfate; The ruthenium precursor is one of ruthenium trichloride, ruthenium nitrite nitrate, ruthenium nitrate, and ruthenium acetate; The molar ratio of the cobalt precursor to the ruthenium precursor is 8:1 to 0.5:1; The molar ratio of citric acid to the total molar ratio of cobalt ions and ruthenium ions is 1:1 to 2:

1.

3. The preparation method according to claim 1, characterized in that, In step (1), the heating and stirring temperature is 50~80℃ and the stirring time is 0.5~2h.

4. The preparation method according to claim 1, characterized in that, In step (2), the support substrate is pretreated before use. The pretreatment steps include: ultrasonically washing the conductive substrate with organic solvent and ultrapure water in sequence, and then drying it. The organic solvent is one or more of methanol, ethanol, acetone, isopropanol, ethylene glycol, DMF, diethyl ether, toluene, chloroform, n-hexane, cyclohexane, ethyl acetate, dichloromethane, acetonitrile, and tetrahydrofuran; The drying temperature is 60~120℃, and the drying time is 10~24h.

5. The preparation method according to claim 1, characterized in that, In step (2), the supporting substrate is one of carbon paper, carbon cloth, conductive glass, nickel felt, titanium mesh, and nickel foam.

6. The preparation method according to claim 1, characterized in that, In step (2), the coating method is one of drip coating, scraping coating, spin coating, or spray coating.

7. The preparation method according to claim 1, characterized in that, In step (2), the temperature of the constant temperature drying is 100~150℃.

8. The preparation method according to claim 1, characterized in that, In step (3), the calcination temperature is 250~400℃, the calcination time is 2~6h, and the heating rate is 2~10℃ / min; The oxygen-containing atmosphere is air, or an O2 / N2 mixture with an oxygen volume fraction of 10% to 50%, or an O2 / Ar mixture with an oxygen volume fraction of 10% to 50%.

9. A cobalt-ruthenium oxide electrode prepared by the preparation method according to any one of claims 1-8, characterized in that, The electrode comprises a supporting substrate and a catalyst layer loaded on the surface of the supporting substrate. The catalyst layer is a cobalt-ruthenium oxide, wherein Ru is incorporated into the Co3O4 lattice. The loading amount of the catalyst layer on the supporting substrate is 0.25~1 mg cm⁻¹. -2 .

10. An application of the cobalt-ruthenium oxide electrode according to claim 9, characterized in that, The electrode is used for the hydrogen evolution reaction in alkaline water electrolysis and serves as the cathode for anion exchange membrane water electrolysis.

Citation Information

Patent Citations

  • Cobalt ruthenium oxide catalytic electrode for nitrate reduction and preparation method thereof

    CN117265585A

  • Ultra-stable low-ruthenium anode catalyst for PEM water electrolysis hydrogen production and preparation method of ultra-stable low-ruthenium anode catalyst

    CN118880391A

  • Ruthenium cobalt oxide self-supporting electrode and preparation method and application thereof

    CN119980295A